PROSPEK PERADABAN ISLAM ABAD 21 - St Halimang; Rahmawati; Riska Maulidyana Takbir; Nadira; Andika; Muh Irham Sya'rawi; Nur Hikmah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Islamic civilization is one of the great civilizations that has made significant contributions to the development of science, technology, culture, and world civilization. Entering the 21st century, Islamic civilization faces very complex dynamics due to the development of globalization, the industrial revolution 4.0, digitalization, and rapid social change. This study aims to analyze the conditions and dynamics of Islamic civilization in the 21st century, identify the various challenges faced, and explain the wisdom of studying Islamic civilization in facing the development of the times. This study uses a library research method with a qualitative descriptive approach. Data were obtained through a review of the Qur'an, hadith, books, scientific journals, and various relevant literature on the development of Islamic civilization. The results of the study indicate that Islamic civilization in the 21st century is undergoing a process of transformation towards the integration of the values ​​of faith and piety with science and technology. On the other hand, Islamic civilization faces challenges in the form of globalization, the secularization of science, the identity crisis of the younger generation, digital disruption, and the weak integration of spiritual values ​​in modern education. Studying Islamic civilization offers numerous lessons, including fostering historical awareness, strengthening Islamic identity, enhancing ethics in the use of technology, fostering tolerance, and fostering a spirit of lifelong learning. Therefore, the future of Islamic civilization is largely determined by the ability of Muslims to integrate Islamic teachings with developments in science and technology without abandoning moral and spiritual values.